2008
DOI: 10.1264/jsme2.23.73
|View full text |Cite
|
Sign up to set email alerts
|

Broad Distribution and Phylogeny of Anaerobic Endophytes of Cluster XIVa Clostridia in Plant Species Including Crops

Abstract: Endophytic clostridia present on various plants as obligate anaerobes were surveyed by terminal restriction fragment length polymorphism (TRFLP) analysis specific to the clostridial 16S rRNA gene. Endophytic clostridia were detected in 10 plant types: sugarcane, cultivated rice, corn, tobacco, soybean, bermuda grass, tall fescue, and three mangrove species. Phylogenetically, cluster XIVa clostridia were detected more frequently than cluster I clostridia in aerial parts. Isolation of clostridia from surface-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Table 1 lists the DDBJ/GenBank/EMBL accession numbers for the 16S rRNA genes and ITS sequences between 16S-and 23S-rRNA that are used in this study. For the phylogenetic analysis, the neighborjoining method and Clustal W were used as described earlier (Saito et al, 2008).…”
Section: Comparative Genomic Hybridizationmentioning
confidence: 99%
“…Table 1 lists the DDBJ/GenBank/EMBL accession numbers for the 16S rRNA genes and ITS sequences between 16S-and 23S-rRNA that are used in this study. For the phylogenetic analysis, the neighborjoining method and Clustal W were used as described earlier (Saito et al, 2008).…”
Section: Comparative Genomic Hybridizationmentioning
confidence: 99%
“…In addition, the sites of colonization and the movement through xylem vessels of G. diazotrophicus within sugarcane plants are controversial (10,11,13). Recently, Saito et al (29) reported a broad distribution and phylogeny of anaerobic endophytes of cluster XIVa clostridia in various plant species including the leaves, stems, stem cuttings and roots of sugarcane. The fixation of N2 by endophytic bacteria has also been suggested in other crops, eg.…”
mentioning
confidence: 99%
“…3A). Obligate anaerobic bacteria have been found as endophytes in several plant species (37). Under upland conditions, an actinobacterial population belonging to the Actinosynnemataceae was greatly increased in UR plants (Fig.…”
Section: Discussionmentioning
confidence: 98%